Assessment of cardiorespiratory fitness by the Ruffier Dickson test and its correlation with lifestyle related factors: a cross sectional study among Pakistani youth - Ehsan, Fatima; Asim, Maleha (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the correlation of physical activity, screen time and anthropometric parameters with cardiorespiratory fitness using the Ruffier Dickson test. Method: The cross-sectional study was conducted at the Riphah International University, Islamabad, Pakistan, from October 2021 to May 2022, and comprised healthy undergraduate medical students of either gender aged 18-23 years. Anthropometric parameters were measured and standardised assessment tools were used to assess screen time and physical activity. Cardiorespiratory fitness was assessed using Ruffier Dickson test. Data was analysed using SPSS 26. Results: Of the 300 subjects, 186(62%) were females and 114(38%) were males. Body mass index, body weight, resting heart rate, height and the level of physical activity were significantly associated with cardiorespiratory fitness (p<0.05). Conclusion: Physical activity, body weight and body mass index could independently predict cardiorespiratory fitness. Key Words: Ruffier Dickson test, Cardiorespiratory fitness, Body mass index, Physical activity, Screen time.